#TITLE_ALTERNATIVE# - WIDHI PUTRA (NIM : 10207009); Pembimbing : Dr-Ing. Suparno Satira, DEA, ERLIANSYAH
In this final project, a PVDF thin film will be made by using a vacuum pump that have vacuum pump rate 28.624 cm3/s and minimum pressure 900 Pa. PVDF thin film will be made on the surface of glass preparat substrate to see the evaporation process of PVDF material to the time of making thin film and Chamber pressure. The diameter of droplets that attached to the surface of the substrate will change with the duration of the experiment. As the model of mechanism of formation thin film by Volmer-Weber, if the time to make thin film getting longer, then the distribution of droplets that have a large diameter will be increase. The pressure of vacuum system that used will also affect the formation of a thin fil on the surface of the substrate, because if the pressure of the system getting lower then the growth of thin films on the surface of the substrate will be faster as well. From that result it can be seen that the model of making a thin film on the surface of the glass substrate from the evaporation of PVDF material will evolve as Volmer-Weber models, while if the time to make thin film getting longer, then the distribution of droplets that have a large diameter will be increased and if the pressure on Chamber getting lower then it will accelerate the development of a thin film on the surface of the substrate.